The Effect of Elevated Temperature on the Lightweight Aggregate Concrete - Ibrahim, Rahel Khalid (Kurdistan Journal of Applied Research, 2017)
The use of lightweight concrete has become widely spread in concrete structures in the last years. Fire can be considered as a destructive hazard that attack concrete structures. In this research the effect of elevated temperature on lightweight aggregate concretes is studied. For this purpose, 81 cube shaped specimens were prepared from three different lightweight aggregate concrete mixes. After moist curing periods for 3, 7 and28 days, the specimens were subjected to ambient and elevated temperatures of 450?C and 650?C for 2hrs.The weight of the specimens before and after exposure to elevated temperatures was determined and the residual strength results for the specimens were compared. The results showed that, the elevated temperature induces a decrease in strength and significant weight losses in lightweight aggregate concrete.